Community empowerment in waste management in Karangwuni, North Magelang - Nur Laila Yuliani; Eka Yudha Adi Setia; Khikma Wintoro; Sefia Tiara Putri; Mifta Shafira Putri; Bella Ayu Kusuma Wardani (Universitas Muhammadiyah Magelang, 2024)
The high production of household waste in Karangwuni Village, North Kramat, poses a significant concern. This community service aimed to enhance public awareness of proper waste management as a preventive measure against diseases, particularly chikungunya. Through methods such as socialization, counseling, and mentoring, the activity successfully increased public awareness of environmental cleanliness and waste management. Additionally, training on herbal drink preparation was provided to PKK mothers to boost immunity.